Lived experience of healthcare professionals providing safe abortion in Rwanda - M. G. S. Musabwasoni; E. Ngoga; B. Sitini; J. Muganda; E. Kanyamanza; G. Nyiringango; O. Tengera; M. C. Uwimana; K. Muganwa; O. Bazirete; M. Mukeshima; T. C. Uhawenimana (Rwanda Medical Journal, 2022)
BACKGROUND: Various countries have ratified the law declaring that safe abortion is a fundamental women’s right. Rwanda has expanded legal grounds for abortion in Law n° 68/2018 of 30/08/2018, determining offenses and penalties in general. This study aimed to gain an in- depth understanding of how physicians, midwives and nurses perceive safe abortion service provision and their experience of providing the service in Rwanda. METHODS: A qualitative, descriptive phenomenological method with transcendental theory devised by Husserl Edmund was used to guide this study. A non-random purposive sampling recruited twenty-three informants, and a semi-structured interview guide was used to collect data. The data analysis used NVivo pro 12 software to categorize and code ideas, while the eight steps of transcendental descriptive phenomenology were used to generate the final themes. RESULTS: Four themes with ten sub-themes were generated: (1) personal feelings and beliefs (humiliation and stigma, guilty and wonder); (2) resilient mechanisms (Clients’ protection, institutional support, appreciation of the law); (3) training and (4) informants’ recommendations (integrated service, community awareness, psychological support, follow-up). CONCLUSION: Healthcare providers’ willingness to provide safe abortion services depend on the individual’s beliefs about abortion. Professionalism and resilient mechanisms are key to sustaining the safe abortion service provision in addition to the law determining offenses and penalties in general in Rwanda.